ANALISIS PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN - Herawati, Niken; Hidayat, Aris; Suwarsito, Suwarsito (Yayasan Akrab Pekanbaru, 2019)
This research aims to identify and analyze the effect of the service quality and price variables toward customer loyalty. Method of data collection in this research is using the survey method with questionnaires. Population in this research is the customers of Speedy in Cimanggis. Based on the results of the analysis, it indicates that the service quality significantly influences the customer loyalty, shown by the t significant value of 0.000 smaller that Î± 0.05 with the regression coefficient of 2.537. service quality has a significant effect on the customer loyalty indicated by the t significant value 0.000 less than Î± =0.05. service quality and price significantly influence the customer loyalty shown by F significant value of 0.000 smaller than Î±=0.05 and are able contribute to the customer loyalty variables of 0.504 or 50.4%. the remaining 49.6% is influenced by other variables that are not examined in this research.